Vanadium cerium oxide composite electrode material and preparation method and application method thereof

CN123017747APending Publication Date: 2026-10-30YINGKOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611351277.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]其中,锰基材料,如MnO2,虽具有多价态、高容量和低成本的优势,但在循环过程中,锰离子易从晶格中溶出,导致容量衰减并腐蚀锌负极,同时,晶体结构易发生不可逆坍塌;普鲁士蓝类似物虽具有开放的三维框架结构、倍率性能好,但在合成过程中引入的大量结晶水会占据储能活性位点,引起晶格膨胀收缩导致结构粉化,并严重降低体积能量密度;钒基材料,如V2O5,凭借钒元素的多价态氧化还原反应提供超高比容量(300-500mAh/g),层状结构也有利于锌离子嵌入脱出,但仍存在两大瓶颈:一是锌离子高电荷密度导致水分子共嵌入,反复的体积膨胀收缩使层状结构坍塌;二是钒基氧化物本征导电性差,离子扩散动力学缓慢,倍率性能受限,铈元素虽具有Ce3+/Ce4+多价态活性可丰富储能位点,但单一铈基材料同样存在导电性差和容量有限的问题

Benefits of technology

[0014]本发明的有益技术效果为:MoS2有优异的导电性与层状结构,利用钒铈氧化物与MoS2的改性策略,打破单一钒基或铈基的材料性能局限,构建高效的离子与电子传输通道,解决传统钒基材料导电性差、离子扩散速率慢的关键问题,实现材料结构与电化学性能的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017747A_ABST
    Figure CN123017747A_ABST
Patent Text Reader

Abstract

The application discloses a vanadium cerium oxide composite electrode material and a preparation method and an application method thereof, and relates to the technical field of composite electrode materials. The composite electrode material is a CeVO4 / MoS2 composite material or a CeVO4@MoS2 composite material. Appropriate amounts of ammonium metavanadate, cerium nitrate and cetyltrimethylammonium bromide are taken as raw materials to prepare cerium vanadate, and then appropriate amounts of sodium molybdate, thioacetamide and the above-mentioned cerium vanadate are taken as raw materials to prepare the composite electrode material. The cerium element is introduced to modify the vanadium-based material, the multivalent state characteristics of the cerium element are utilized to enrich the oxidation and reduction active sites of the material, and the specific capacity of the material is improved. Meanwhile, the introduction of MoS2 can inhibit the dissolution of active substances in the vanadium cerium oxide, relieve the collapse of the electrode structure, significantly improve the cycle stability of the capacitor, and break through the bottleneck of short cycle life and fast capacity attenuation of traditional vanadium-based positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of composite electrode materials, specifically a vanadium-cerium oxide composite electrode material and its preparation and application methods. Background Technology

[0002] Aqueous zinc-ion capacitors have become a research hotspot in the energy storage field due to the safety of their non-flammable and non-explosive aqueous electrolytes and the advantages of abundant reserves and high theoretical specific capacity of metallic zinc anodes. Among them, the cathode material is the core component that determines the energy density, power density and cycle life of the capacitor. In the existing technology, the cathode materials of aqueous zinc-ion capacitors are mainly three categories of materials: manganese-based, Prussian blue analogues and vanadium-based materials.

[0003] Among them, manganese-based materials, such as MnO2, have the advantages of multiple valence states, high capacity, and low cost. However, during cycling, manganese ions easily dissolve from the crystal lattice, leading to capacity decay and corrosion of the zinc anode. Simultaneously, the crystal structure is prone to irreversible collapse. Prussian blue analogues, while possessing an open three-dimensional framework structure and good rate performance, suffer from the problem of a large amount of water of crystallization introduced during synthesis occupying energy storage active sites, causing lattice expansion and contraction leading to structural pulverization and severely reducing volumetric energy density. Vanadium-based materials, such as V2O5, provide ultra-high specific capacity (300-500 mAh / g) through the redox reactions of vanadium's multiple valence states. The layered structure also facilitates zinc ion insertion and extraction. However, two major bottlenecks remain: first, the high charge density of zinc ions leads to water molecule co-intercalation, and repeated volume expansion and contraction cause the layered structure to collapse; second, vanadium-based oxides have poor intrinsic conductivity and slow ion diffusion kinetics, limiting rate performance. While cerium has Ce... 3+ / Ce 4+ Multivalent activity can enrich energy storage sites, but single cerium-based materials also suffer from poor conductivity and limited capacity. Summary of the Invention

[0004] To address the aforementioned problems, specifically those raised in the background section, this invention proposes a vanadium-cerium oxide composite electrode material, its preparation method, and its application method. The specific technical solution is as follows: A vanadium-cerium oxide composite electrode material, wherein the composite electrode material is a CeVO4 / MoS2 composite material or a CeVO4@MoS2 composite material.

[0005] Preferably, when the composite electrode material is a CeVO4 / MoS2 composite material, the raw materials of the CeVO4 / MoS2 composite material include cerium vanadate, sodium molybdate and thioacetamide, wherein the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

[0006] Preferably, when the composite electrode material is a CeVO4@MoS2 composite material, the raw materials of the CeVO4@MoS2 composite material include cerium vanadate, sodium molybdate and thioacetamide, wherein the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

[0007] A method for preparing a vanadium-cerium oxide composite electrode material, the method comprising: Take appropriate amounts of ammonium metavanadate, cerium nitrate and hexadecyltrimethylammonium bromide as raw materials and mix them to obtain a raw material mixture; Add an appropriate amount of water to the raw material mixture to obtain a raw material solution; The raw material solution was magnetically stirred to obtain a homogeneous mixture; The pH of the homogeneous mixture was adjusted to 9.5 to 10.5 to obtain the adjusted mixture; The adjusted mixture was transferred to an autoclave, which was then placed in an oven. The reaction was carried out at a first temperature for a first duration, with the first temperature being greater than or equal to 155°C and less than or equal to 165°C, and the first duration being greater than or equal to 11.5 h and less than or equal to 12.5 h, to obtain the reactants after the high-temperature reaction. The reactants after the high-temperature reaction were naturally cooled to room temperature to obtain reactants at room temperature. The reactants at room temperature were filtered to obtain a solid. The solid was dried at room temperature for a second time, which was greater than or equal to 23.5 h and less than or equal to 24.5 h, to obtain the dried product. The dried product is ground to obtain a powdered product; The powdered product was calcined at a second temperature for a third time, the second temperature being greater than or equal to 390°C and less than or equal to 410°C, and the third time being greater than or equal to 1.5 h and less than or equal to 2.5 h, to obtain cerium vanadate. Composite electrode materials were prepared by using appropriate amounts of sodium molybdate, thioacetamide, and cerium vanadate as raw materials.

[0008] Preferably, when the composite electrode material is a CeVO4 / MoS2 composite material, appropriate amounts of sodium molybdate, thioacetamide, and cerium vanadate are used as raw materials, and the specific steps for preparing the composite electrode material include: Weigh an appropriate amount of sodium molybdate and dissolve it in an appropriate amount of distilled water. Sonicate the solution until it is completely dissolved to obtain a sodium molybdate solution. Weigh an appropriate amount of thioacetamide and dissolve it in an appropriate amount of distilled water. Sonicate the solution until it is completely dissolved to obtain a thioacetamide solution. Sodium molybdate solution and thioacetamide solution were mixed and stirred continuously during the mixing process to obtain MoS2 solution; Weigh an appropriate amount of cerium vanadate and mix it with MoS2 solution to obtain CeVO4 / MoS2 solution; The CeVO4 / MoS2 solution was reacted at a third temperature for a second time. The third temperature was greater than or equal to 210℃ and less than or equal to 230℃ to obtain the heated CeVO4 / MoS2 solution. The heated CeVO4 / MoS2 solution was naturally cooled to room temperature to obtain a room temperature CeVO4 / MoS2 solution. The CeVO4 / MoS2 solution at room temperature was filtered to obtain solid CeVO4 / MoS2. Solid CeVO4 / MoS2 is dried at a fourth temperature for a first time, the fourth temperature being greater than or equal to 55°C and less than or equal to 65°C, to obtain a CeVO4 / MoS2 composite material.

[0009] Preferably, when the composite electrode material is a CeVO4@MoS2 composite material, the preparation method includes: Take appropriate amounts of sodium molybdate, thioacetamide and cerium vanadate, place them in a polytetrafluoroethylene reaction vessel, add distilled water to obtain a mixed solution; Adjust the pH of the mixed solution to 10 to obtain the adjusted mixed solution; The adjusted mixture is stirred magnetically until homogeneous, resulting in a uniform mixture. The homogeneous mixed solution was transferred to an autoclave and placed in an oven. The reaction was carried out at a constant temperature for a second time at a third temperature greater than or equal to 210°C and less than or equal to 230°C to obtain the CeVO4@MoS2 solution after the reaction. The CeVO4@MoS2 solution after the reaction was naturally cooled to room temperature to obtain a CeVO4@MoS2 solution at room temperature. CeVO4@MoS2 at room temperature was filtered to obtain CeVO4@MoS2 solid; CeVO4@MoS2 solid was dried at room temperature for a second time to obtain CeVO4@MoS2 composite material.

[0010] Preferably, in the step of mixing appropriate amounts of ammonium metavanadate, cerium nitrate, and hexadecyltrimethylammonium bromide as raw materials, the molar ratio of cerium nitrate to ammonium metavanadate is 2 to 8, and the amount of hexadecyltrimethylammonium bromide added is 0.0685 to 0.137 parts based on the molar amount of ammonium metavanadate added.

[0011] Preferably, in the steps of weighing an appropriate amount of sodium molybdate and dissolving it in an appropriate amount of distilled water, and weighing an appropriate amount of thioacetamide and dissolving it in an appropriate amount of distilled water, the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

[0012] Preferably, in the step of taking appropriate amounts of sodium molybdate, thioacetamide, and cerium vanadate, placing them in a polytetrafluoroethylene reactor, and adding distilled water to obtain a mixed solution, the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

[0013] A method for applying a vanadium-cerium oxide composite electrode material, wherein the composite electrode material is a vanadium-cerium oxide composite electrode material prepared by the above preparation method, and the vanadium-cerium oxide composite electrode material is used as an electrode material for a supercapacitor.

[0014] The beneficial technical effects of this invention are as follows: MoS2 has excellent conductivity and layered structure. By using the modification strategy of vanadium cerium oxide and MoS2, the limitations of the performance of single vanadium-based or cerium-based materials are broken, and efficient ion and electron transport channels are constructed. This solves the key problems of poor conductivity and slow ion diffusion rate of traditional vanadium-based materials, and achieves synergistic improvement of material structure and electrochemical performance.

[0015] Introducing cerium to dope vanadium-based materials enhances their redox active sites and specific capacity by utilizing the multivalent state characteristics of cerium. Simultaneously, the introduction of MoS2 can suppress the dissolution of active substances in vanadium-cerium oxides, alleviate electrode structure collapse, and significantly improve the cycle stability of capacitors, breaking through the bottleneck of short cycle life and rapid capacity decay of traditional vanadium-based cathode materials. Attached Figure Description

[0016] Figure 1 This is a cyclic voltammetry test curve for group 1 in Embodiment 1 of the present invention; Figure 2 This is a cyclic voltammetry test curve for group 2 in Embodiment 1 of the present invention; Figure 3 This is a cyclic voltammetry test curve for group 3 in Embodiment 1 of the present invention; Figure 4 This is a constant current charge-discharge test curve for group 1 in Embodiment 1 of the present invention; Figure 5 This is a constant current charge-discharge test curve for group 2 in Embodiment 1 of the present invention; Figure 6 This is a constant current charge-discharge test curve for group 3 in Embodiment 1 of the present invention; Figure 7The graph shows the AC impedance test results of the three groups of supercapacitors in Embodiment 1 of the present invention. Figure 8 This is a cyclic voltammetry test curve for group 2 in Embodiment 2 of the present invention; Figure 9 This is a cyclic voltammetry test curve for group 1 in Embodiment 2 of the present invention; Figure 10 This is a cyclic voltammetry test curve for group 3 in Embodiment 2 of the present invention; Figure 11 This is a constant current charge-discharge test curve for group 2 in Embodiment 2 of the present invention; Figure 12 This is a constant current charge-discharge test curve for group 1 in Embodiment 2 of the present invention; Figure 13 This is a constant current charge-discharge test curve for group 3 in Embodiment 2 of the present invention; Figure 14 The graph shows the AC impedance test results of the three groups of supercapacitors in Embodiment 2 of the present invention. Figure 15 This is a cyclic voltammetry test curve for group 2 in Embodiment 3 of the present invention; Figure 16 This is a cyclic voltammetry test curve for group 1 in Embodiment 3 of the present invention; Figure 17 This is a cyclic voltammetry test curve for group 3 in Embodiment 3 of the present invention; Figure 18 This is a constant current charge-discharge test curve for group 2 in Embodiment 3 of the present invention; Figure 19 This is a constant current charge-discharge test curve for group 1 in Embodiment 3 of the present invention; Figure 20 This is a constant current charge-discharge test curve for group 3 in Embodiment 3 of the present invention; Figure 21 These are the electrochemical impedance spectra of the three groups of supercapacitors in Example 3 of the present invention. Detailed Implementation

[0017] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0018] Example 1: Preparation of cerium vanadate (CeVO4) Cerium vanadate was prepared by a hydrothermal method using ammonium metavanadate, cerium nitrate, and hexadecyltrimethylammonium bromide (CTAB) as raw materials. The ammonium metavanadate and cerium nitrate were taken in molar ratios of 1:2, 1:4, and 1:8, and the molar amount of CTAB was 0.137 parts. The raw materials were divided into three groups and mixed to obtain a raw material mixture. The raw material ratios of the three groups are shown in Table 1.

[0019] Table 1. Cerium vanadate raw material ratio table

[0020] After mixing the three raw materials separately and thoroughly, 12 mL of distilled water was added, and the mixture was dispersed using a magnetic stirrer for 30 minutes until homogeneous. The homogeneous mixture was then transferred to the lining of a 25 mL autoclave, the pH was adjusted to approximately 10, and the autoclave was placed in an oven and reacted at 160°C for 12 hours. After the reaction was complete, the autoclave was allowed to cool naturally to room temperature, and then filtered. The filtered solid was dried at room temperature for 24 hours, and the dried product was collected. The dried product was ground into powder and placed in a box-type resistance furnace, where it was baked at 400°C for 2 hours to obtain cerium vanadate. Three sets of cerium vanadate products were used as electrode materials for supercapacitors to prepare supercapacitors, resulting in three sets of supercapacitors.

[0021] Cyclic voltammetry tests were performed on three sets of supercapacitors, with a scan rate range of 10 mV / s. The cyclic voltammetry test curves for the three sets are shown below. Figures 1 to 3 As shown in the figure, the supercapacitor in group 2 has a larger cyclic voltammetry curve area, higher peak current, and larger specific capacitance, indicating superior performance compared to groups 1 and 3.

[0022] Constant current charge-discharge tests were conducted on three groups of supercapacitors. The current density during the test was 1 A·g. -1 2A·g -1 ,4A·g -1 8A·g -1 The constant current charge-discharge test curves of the three sets of supercapacitors are as follows: Figures 4 to 6 As shown.

[0023] As can be seen from the figure, during the experiment, the current of the three groups of supercapacitors changed from 1 A·g -1 Gradually increase to 8A·g -1 The charging and discharging times shortened accordingly, but the curve profile remained almost unchanged, indicating that the charge storage mechanism was relatively stable over a wide current range. The charging and discharging plateau was clearly visible, and the potential difference increased only slightly with increasing current, suggesting rapid charge transport and ion diffusion in the material, and minimal polarization under high current. The high crystallinity and porous, interwoven morphology of the supercapacitor in group 2 provided a good structural basis for rapid charge storage, even at 8 A·g.-1 It can still maintain a relatively long discharge time, demonstrating outstanding rate performance; however, the curve of sample group 1 is highly sensitive to current, only showing a discharge rate of 1 A·g. -1 and 2A·g -1 Normal charging and discharging processes can still be observed at this time, but once the current increases to 4 A·g -1 or 8A·g -1 The charge / discharge time shortened drastically, the curve almost became a straight line, the charge / discharge plateau disappeared, and polarization increased significantly. This indicates that ion diffusion and charge transport are hindered at high currents, resulting in poor rate performance. The overall discharge time was also significantly shorter than that of Group 2 samples, and the storage capacity and kinetic response were significantly weaker. The situation of Group 3 samples was similar to that of Group 1 samples, but the performance degradation was more severe. Only at 1 A·g -1 The lower curve is relatively complete, 2A·g -1 The charge / discharge times were significantly reduced, and the curves were severely distorted. At low to medium current densities, the charge / discharge plateau was already indistinct, and the polarization effect was strong. This is likely because the dense, bulky aggregate structure severely hindered ion transport, resulting in poor adaptability of the material to current changes. Its discharge time was the shortest of the three samples, indicating low utilization of active sites and poor electrochemical kinetics.

[0024] In summary, sample 2 exhibited the longest discharge time and the highest specific capacity at all current densities, with a discharge value of 8 A·g. -1 The capacity retention was also excellent, and its rate performance was significantly better than that of samples from groups 1 and 3. Furthermore, it exhibited the smallest charge-discharge potential difference, with limited increase in potential with increasing current, indicating low internal resistance and charge transfer resistance.

[0025] AC impedance tests were performed on three groups of supercapacitors, and the test results are as follows: Figure 7 As shown. According to Figure 7 As can be seen, the high-frequency region is a semicircle, while the low-frequency region is a slanted line. The diameter of the semicircle represents the charge transfer resistance (Rct). The smaller the diameter, the less resistance there is to the charge passing through the electrode / electrolyte interface.

[20] The slope of the low-frequency line reflects the speed of ion diffusion; the larger the slope, the faster the ion diffusion and the more ideal the capacitance characteristics. The intercepts of the three samples in the high-frequency region with the real axis are all small and similar, meaning that the equivalent series resistance (Rs) is not significantly different, and the ohmic contact of the test system is good. Regarding charge transfer resistance: the semicircle of sample 1 is the smallest, indicating the smoothest charge interface transport; the semicircle of sample 2 is slightly larger, with a slight increase in resistance; the semicircle of sample 3 is significantly the largest, with charge transfer resistance much higher than the other two, indicating poorer interface charge transfer kinetics. In terms of ion diffusion: the slope of the low-frequency line is the largest for sample 3, followed by sample 2, with sample 1 having the lowest slope. While the slope alone seems to indicate the fastest ion diffusion in group 3, its Rct is too large, and the overall kinetics are still insufficient. Group 2 has a larger slope, and its charge transfer resistance is not high, making its rate performance outstanding under high current. Although group 1 has the lowest Rct, its ion diffusion is not keeping up, which limits its charge storage capacity. The sample in group 1 exhibits the lowest charge transport resistance and facilitates electron exchange, but its charge storage and cyclic voltammetry performance are generally poor, indicating that the main issues lie in ion diffusion and active site utilization. The sample in group 2 demonstrates moderate charge transfer resistance and a relatively fast ion diffusion rate, resulting in a good kinetic match between electron and ion processes. This is the key reason for its superior rate performance and specific capacity. The sample in group 3 exhibits excessively high charge transfer resistance and severe interfacial polarization, naturally leading to the worst charge storage performance.

[0026] Based on the combined results of the cyclic voltammetry test, constant current charge-discharge test, and AC impedance test of the three groups of supercapacitors, the supercapacitor in group 2 exhibits superior performance compared to the other two groups. Therefore, cerium vanadate in group 2 was selected as the raw material for the electrode material described in this invention.

[0027] Example 2 Preparation of CeVO4 / MoS2 composite material Sodium molybdate and thioacetamide were used as raw materials and divided into three groups according to mass ratios of 1:2, 1:1 and 1:0.5. The raw material amounts of the three CeVO4 / MoS2 composite materials are shown in Table 2.

[0028] Table 2 Raw material quantities of CeVO4 / MoS2 composite materials

[0029] All three raw materials were dissolved in 15 mL of distilled water and ultrasonically vibrated until completely dissolved. For each composite material, the clear solution of one raw material was poured into the other clear solution while continuously stirring. After complete mixing, 0.015 g of the cerium vanadate sample from group 2 of Example 1 was added to the mixed solution to obtain a CeVO4 / MoS2 mixed solution. The CeVO4 / MoS2 mixed solution was reacted at 220 °C for 24 h. After the reaction vessel cooled naturally to room temperature, it was filtered. The solid obtained after filtration was dried in a vacuum drying oven at 60 °C for 12 h. The dried product was the CeVO4 / MoS2 composite material. Supercapacitors were prepared using the three CeVO4 / MoS2 composite materials as electrode materials, resulting in three supercapacitors.

[0030] Cyclic voltammetry tests were performed on three groups of supercapacitors, and the test results are as follows: Figures 8 to 10 As shown in the figure, the closed area of ​​the cyclic voltammetry test curve is the highest among the three groups of samples in Group 2. The peak position shift is small and the polarization is weak across the entire scan rate range, indicating the best redox reversibility and electrochemical energy storage performance. Compared to the Group 2 sample, the peak current and closed area are significantly lower in Group 1 at the same scan rate, with increased peak position shift and polarization at higher scan rates. Excessive agglomerated MoS2 hinders electrolyte penetration into the matrix, increases electrode interface impedance, and redundant inactive agglomerated components reduce the overall effective specific capacity. In Group 3, the insufficient Mo source makes it difficult to construct a complete conductive network between CeVO4 particles.

[0031] Constant current charge-discharge tests were performed on three groups of supercapacitors, and the test results are as follows: Figures 11 to 13 As shown in the figure, the discharge duration of each charge-discharge curve for sample group 2 is the longest, corresponding to the highest specific capacity. Simultaneously, the initial potential drop during charge-discharge is the smallest among the three groups, indicating that the composite heterostructure effectively reduces ohmic impedance and charge transfer impedance. With current density increasing from 1 A·g... -11 Upgraded to 8A·g -1 The capacity decay of sample group 2 was much lower than that of the other two groups, demonstrating excellent high current tolerance and rate stability.

[0032] Electrochemical impedance spectroscopy was performed on three groups of supercapacitors, and the test results are as follows: Figure 14 As shown, from Figure 14 As can be seen, the curve for Group 1 has the steepest slope in the low-frequency range, approaching vertical, indicating lower impedance and the lowest solid-phase diffusion resistance of electrolyte ions in the electrode channels and inside the material. The slope of the low-frequency curve for Group 3 is significantly smaller, indicating that CeVO4 agglomeration blocks the ion channels, resulting in the worst ion diffusion kinetics. The sample in Group 2 has the lowest charge transfer impedance and the best ion diffusion performance.

[0033] Example 3 Preparation of CeVO4@MoS2 composite material Sodium molybdate, thioacetamide, and cerium vanadate sample from Group 2 of Example 1 were used as raw materials and divided into 3 groups according to different mass ratios. The mass ratios of sodium molybdate and thioacetamide in the raw materials were 1:2, 1:1, and 1:0.5, respectively. The raw material amounts of the CeVO4@MoS2 composite materials in the 3 groups are shown in Table 3.

[0034] Table 3 Raw material quantities of CeVO4@MoS2 composite materials

[0035] Three CeVO4@MoS2 composite materials were prepared by placing sodium molybdate and thioacetamide into 25 mL polytetrafluoroethylene reactors according to their respective mass ratios. 0.015 g of cerium vanadate sample was added, followed by 12 mL of distilled water to adjust the pH to approximately 10. Magnetic stirring was then applied to disperse the mixture for 30 minutes until homogeneous. The homogeneous mixture was then transferred to the lining of a 25 mL autoclave and placed in an oven. The reaction was carried out at 220 °C for 24 h. After the reactor cooled naturally to room temperature, it was filtered, and the solid was collected. The solid was dried at room temperature for 24 h, and the collected product was the CeVO4@MoS2 composite material. Three CeVO4@MoS2 composite materials were used as electrode materials to prepare supercapacitors, resulting in three sets of supercapacitors.

[0036] Cyclic voltammetry tests were performed on three groups of supercapacitors, and the test results are as follows: Figures 15 to 17 As shown in the figure, the sample line of group 2 exhibits good smoothness and regularity at different scan rates. The linear relationship between peak current and scan rate is clear, and the symmetry of the redox peaks is excellent at low to medium scan rates, with small peak position differences. As the scan rate increases from 10 mV / s to 100 mV / s, the curve shows no obvious distortion or broadening, and the peak current increases linearly with the scan rate, indicating that the material can still maintain good charge transport and ion diffusion capabilities at high scan rates. The figure for group 3 shows significant fluctuations, indicating that insufficient Mo content leads to conductivity deficiencies, and excessive current exacerbates current fluctuations, resulting in poor material performance at this ratio.

[0037] Constant current charge-discharge tests were performed on three groups of supercapacitors, and the test results are as follows: Figures 18 to 20 As shown in the figure, the discharge time of group 2 decreases proportionally with increasing current, without any sudden capacity drop or curve distortion, and at 4A·g -1 and 8A·g -1 Discharge profile at high rate and 1 A·g -1 and 2A·g -1The curves at low rates highly overlap. This reflects that the synergistic effect between the active components is optimal at this ratio, the pore structure and conductive network ensure rapid ion transport, outstanding rate capacity retention, and the best overall charge storage performance among the three. Group 1 shows a shorter discharge time, a significant decrease in low-rate specific capacity, reduced material utilization, and overall electrochemical performance inferior to Group 2. Group 3 exhibits the worst charge storage kinetics, with the voltage plateau in the charge-discharge curve completely lost at 4 A·g -1 and 8A·g -1 The effective discharge range is almost nonexistent, and the usable capacity decays rapidly. The low content of key active components in this formulation not only results in a severe shortage of charge storage sites but also disrupts the material's conductivity continuity, leading to a sharp increase in ion diffusion resistance. During charge and discharge, the coupling between concentration polarization and ohmic polarization intensifies, severely restricting the charge storage kinetics of the electrode.

[0038] Electrochemical impedance spectroscopy (EIS) was performed on three groups of supercapacitors, and the obtained EIS spectra are shown below. Figure 21 As shown. Figure 21 As shown, all three sample ratios exhibit low ohmic impedance in the high-frequency region, with similar solution resistance, indicating good contact between the electrolyte and electrode materials and essentially equivalent ion transport paths. In the mid-frequency region, each sample exhibits a typical capacitive arc, with the arc radius directly related to the interfacial charge transfer resistance. Among them, sample group 2 has the smallest semicircle diameter and the lowest charge transfer impedance, indicating that the electron conduction kinetics at the heterojunction are optimal at this ratio, significantly improving charge separation and interfacial transport efficiency. In contrast, sample group 3, due to its low MoS2 content, failed to form a continuous and complete conductive network, resulting in obstructed charge transport paths at the interface and a significantly increased charge transfer resistance. Further analysis reveals that an appropriate and uniform MoS2 coating can effectively construct a highly conductive interface, providing a fast electron transport channel while maintaining good structural stability; however, an excessively low MoS2 loading is insufficient to fully couple CeVO4 with the conductive network, limiting the efficient utilization of interfacial electrochemical active sites. Therefore, group 2 exhibits the best impedance performance, demonstrating optimal electrochemical kinetic behavior.

[0039] Comparing the three supercapacitors in Example 2 and Example 3, in the cyclic voltammetry test, group 2 showed the largest curve area and peak current in both methods, demonstrating superior performance compared to the other two ratios. An appropriate amount of MoS2 can build a continuous conductive network, dispersing CeVO4 and inhibiting aggregation. In the three groups, insufficient MoS2 prevented the formation of a complete conductive pathway, leading to excessive CeVO4 stacking and clogging of ion channels, increasing internal resistance and exacerbating polarization. When the MoS2 ratio was increased to 1:1, the conductive framework and active CeVO4 were balanced, balancing conductivity and the number of active sites. Further increasing the MoS2 ratio to 1:2 resulted in excessive MoS2 diluting the proportion of active components, causing a simultaneous decrease in capacity and kinetics.

[0040] This application first prepared CeVO4 as a substrate electrode material in ratios of 1:2, 1:4, and 1:8 using a hydrothermal synthesis method. First, three-electrode experiments and basic performance characterization were conducted on the basic samples. The results showed that CeVO4 performed best at a 1:4 ratio, exhibiting the longest charge-discharge time and a larger enclosed area under cyclic voltammetry, demonstrating particularly outstanding electrochemical performance. To improve the stability of CeVO4, it was coated with MoS2, resulting in CeVO4@MoS2 composite materials. The coating thickness was controlled using different ratios of 1:1, 1:2, and 1:0.5, and three-electrode electrochemical performance tests were performed, including cyclic voltammetry, constant current charge-discharge testing, and electrochemical impedance spectroscopy. The results showed that a 1:1 coating ratio could effectively improve the stability of CeVO4. To investigate which type of MoS2 was more effective for CeVO4, doping was performed to obtain CeVO4 / MoS2 composite materials. The same ratio was used to control the molybdenum content. Three-electrode electrochemical performance tests showed that the performance of the doped material was lower than that of the coated material, exhibiting poorer stability. Comparisons in three-electrode system tests, including CV, GCD, and EIS, showed that CeVO4 exhibits a longer discharge time and greater capacity at a current density of 1 A·g⁻¹. -1 The discharge time can reach 800s, and it has lower impedance.

[0041] Although the invention has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of the invention. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. The invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

[0042] The term "comprising" or any other similar term is intended to cover non-exclusive inclusion, such that a process, article, or apparatus / device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to those processes, articles, or apparatus / devices.

[0043] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after such changes or substitutions will all fall within the scope of protection of the present invention.

Claims

1. A vanadium-cerium oxide composite electrode material, characterized in that, The composite electrode material is a CeVO4 / MoS2 composite material or a CeVO4@MoS2 composite material.

2. The vanadium-cerium oxide composite electrode material according to claim 1, characterized in that, When the composite electrode material is a CeVO4 / MoS2 composite material, the raw materials of the CeVO4 / MoS2 composite material include cerium vanadate, sodium molybdate, and thioacetamide, wherein the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

3. The vanadium-cerium oxide composite electrode material according to claim 1, characterized in that, When the composite electrode material is a CeVO4@MoS2 composite material, the raw materials of the CeVO4@MoS2 composite material include cerium vanadate, sodium molybdate, and thioacetamide, wherein the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

4. A method for preparing a vanadium-cerium oxide composite electrode material, characterized in that, The preparation method is used to prepare the composite electrode material as described in claim 1, and the preparation method includes: Take appropriate amounts of ammonium metavanadate, cerium nitrate and hexadecyltrimethylammonium bromide as raw materials and mix them to obtain a raw material mixture; Add an appropriate amount of water to the raw material mixture to obtain a raw material solution; The raw material solution was magnetically stirred to obtain a homogeneous mixture; The pH of the homogeneous mixture is adjusted to 9.5 to 10.5 to obtain the adjusted mixture; The adjusted mixture is transferred to an autoclave, which is then placed in an oven and reacted at a first temperature for a first duration. The first temperature is greater than or equal to 155°C and less than or equal to 165°C, and the first duration is greater than or equal to 11.5 h and less than or equal to 12.5 h, to obtain the reactants after high-temperature reaction. The reactants after the high-temperature reaction were naturally cooled to room temperature to obtain reactants at room temperature. The reactants at room temperature were filtered to obtain a solid. The solid was dried at room temperature for a second time, the second time being greater than or equal to 23.5 h and less than or equal to 24.5 h, to obtain the dried product; The dried product is ground to obtain a powdered product; The powdered product is calcined at a second temperature for a third time, wherein the second temperature is greater than or equal to 390°C and less than or equal to 410°C, and the third time is greater than or equal to 1.5 h and less than or equal to 2.5 h, to obtain cerium vanadate. The composite electrode material is prepared by taking appropriate amounts of sodium molybdate, thioacetamide, and cerium vanadate as raw materials.

5. The method for preparing the vanadium-cerium oxide composite electrode material according to claim 4, characterized in that, When the composite electrode material is a CeVO4 / MoS2 composite material, the step of preparing the composite electrode material by taking appropriate amounts of sodium molybdate, thioacetamide, and cerium vanadate as raw materials specifically includes: Weigh an appropriate amount of sodium molybdate and dissolve it in an appropriate amount of distilled water. Sonicate the solution until it is completely dissolved to obtain a sodium molybdate solution. Weigh an appropriate amount of thioacetamide and dissolve it in an appropriate amount of distilled water. Sonicate the solution until it is completely dissolved to obtain a thioacetamide solution. The sodium molybdate solution and the thioacetamide solution were mixed and stirred continuously during the mixing process to obtain a MoS2 solution; Weigh an appropriate amount of the cerium vanadate and mix it with the MoS2 solution to obtain a CeVO4 / MoS2 solution; The CeVO4 / MoS2 solution is reacted at a third temperature for the second time, wherein the third temperature is greater than or equal to 210°C and less than or equal to 230°C, to obtain a heated CeVO4 / MoS2 solution. The heated CeVO4 / MoS2 solution was naturally cooled to room temperature to obtain a room temperature CeVO4 / MoS2 solution. The room temperature CeVO4 / MoS2 solution was filtered to obtain solid CeVO4 / MoS2; The solid CeVO4 / MoS2 is dried at a fourth temperature for a first duration, wherein the fourth temperature is greater than or equal to 55°C and less than or equal to 65°C, to obtain a CeVO4 / MoS2 composite material.

6. The method for preparing the vanadium-cerium oxide composite electrode material according to claim 4, characterized in that, When the composite electrode material is a CeVO4@MoS2 composite material, the preparation method includes: Take an appropriate amount of sodium molybdate, thioacetamide and cerium vanadate, place them in a polytetrafluoroethylene reaction vessel, add distilled water to obtain a mixed solution; Adjust the pH of the mixed solution to 10 to obtain the adjusted mixed solution; The adjusted mixture is stirred magnetically until homogeneous to obtain a uniform mixture. The homogeneous mixed solution is transferred to an autoclave and placed in an oven. The reaction is carried out at a third temperature for the second duration, wherein the third temperature is greater than or equal to 210°C and less than or equal to 230°C, to obtain the CeVO4@MoS2 solution after the reaction. The CeVO4@MoS2 solution after the reaction was naturally cooled to room temperature to obtain a CeVO4@MoS2 solution at room temperature. The room temperature CeVO4@MoS2 was filtered to obtain CeVO4@MoS2 solid. The CeVO4@MoS2 solid was dried at room temperature for the second time to obtain the CeVO4@MoS2 composite material.

7. The method for preparing the vanadium-cerium oxide composite electrode material according to claim 4, characterized in that, In the step of mixing appropriate amounts of ammonium metavanadate, cerium nitrate, and hexadecyltrimethylammonium bromide as raw materials, the molar ratio of cerium nitrate to ammonium metavanadate is 2 to 8, and the amount of hexadecyltrimethylammonium bromide added is 0.0685 to 0.137 parts based on the molar amount of ammonium metavanadate.

8. The method for preparing the vanadium-cerium oxide composite electrode material according to claim 5, characterized in that, In the steps of weighing an appropriate amount of sodium molybdate and dissolving it in an appropriate amount of distilled water, and in the steps of weighing an appropriate amount of thioacetamide and dissolving it in an appropriate amount of distilled water, the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

9. The method for preparing the vanadium-cerium oxide composite electrode material according to claim 5, characterized in that, In the step of taking appropriate amounts of sodium molybdate, thioacetamide, and cerium vanadate, placing them in a polytetrafluoroethylene reaction vessel, and adding distilled water to obtain a mixed solution, the molar amount of sodium molybdate is 0.093 to 0.744 parts, the molar amount of thioacetamide is 1.20 to 4.80 parts, and the amount of cerium vanadate added is 0.0588 parts.

10. A method for applying a vanadium-cerium oxide composite electrode material, characterized in that, The composite electrode material is the vanadium-cerium oxide composite electrode material prepared by any one of the preparation methods described in claims 4 to 9, and the vanadium-cerium oxide composite electrode material is used as an electrode material for a supercapacitor.